Ensaio clínico com peeling de ácido glicólico 70% como coadjuvante no tratamento das onicomicoses em pacientes atendidos em hospital terciário de Cuiabá - MT - Chagas, Luna Albertini (2020)
Onychomycosis is a fungal infection that affects approximately 10% of the population, characterized as cosmopolitan. Clinical changes range from onycholysis, variations in color and texture of the nail. Available treatments include: topical, systemic, chemical abrasion, photodynamic therapy and lasers. Combined treatments increase the chances of healing, however, the aesthetic improvement of the compromised nail bed currently represents a great challenge. This study aimed to conduct a clinical trial with the comparison of two groups, randomized and double-blind, of patients with onychomycosis, who received topical treatment with cyclopirox olamine 8% lacquer in monotherapy and treatment with cyclopirox olamine 8% associated with 70% glycolic acid peel formulated at pH equal to 1.5. Dermatophyte or non-dermatophyte filamentous fungi isolated on fingernails or toenails were included as etiologic agents. 265 samples were collected, of which 104 were eligible for the study and 43 completed follow-up for six months. Of the 43 nails, 25 were allocated to the group that received AG 70% and ciclopirox olamine 8% lacquer and 18 were selected for the placebo group (water and propylene glycol). It was observed that there was a statistically significant reduction in the proportion of positive cultures in the third month and sixth month when compared with the proportion of positive cultures initially performed. When comparing the mean scores of the OSI classification of the independent examiners, a significant reduction was observed in the post-treatment of the group that used AG peeling when compared to the placebo group.